THE ROLE OF INSURANCE IN ANTICIPATING THE RISK OF DEFAULT IN PEER TO PEER (P2P) LENDING SCHEME - Ida Ayu Rhadana Satvikarani; Mas Rahmah; Dian Purnama Anugerah (Universitas Airlangga, 2021)
The presence of fintech in Indonesia is said as an answer of people needs about the ease on transaction and financing in business activity. According to Article 3 of POJK No.77 of 2016 concerning Information Technology-Based Money Lending Services, it is explained that Information Technology-based Money Lending Service is the implementation of financial services to bring lenders together with borrowers in order to make loan agreements in rupiah currency directly through electronic systems using internet networks commonly referred to as Peer to Peer (P2P) Lending. Commonly when the default in P2P Lending exist, the role of insurance is to mitigate the risk in order to support lender protection. This study reviewed the risk of default in P2P lending schemes, within discussion of insurance role in doing mitigation of default risk in P2P lending. This legal research uses normative juridical research method with statute approach and conceptual approach. The study result explain that P2P Lending is a form of investment, in which every investment must have a risk, and this risk is directly proportional to the high risk high return. Default or often referred to as non-performing loan (NPL) is a situation where borrowers are late to return principal of the loan more than 90 days from maturity time, therefore risk mitigation is important. The purpose of insurance scheme in P2P Lending fintech services is an effort to overcome losses suffered by lenders.